Case Report: Clinical analysis of a cluster outbreak of chlamydia psittaci pneumonia - Wu, Yinxia; Xu, Xuemei; Liu, Yun; Jiang, Xiangwei; Wu, Hongjing; Yang, Jie; He, Limei (Frontiers in Cellular and Infection Microbiology, 2023)
Objective: To explore the clinical characteristics and prognosis of clustered cases of psittacosis pneumonia. Method: We retrospectively analyzed the clinical data of a cluster outbreak of psittacosis pneumonia. The analysis included epidemiological data, clinical symptoms, laboratory results, and prognosis. The diagnosis was made using mNGS and nested PCR technology. Result: Of the four cases, two had direct contact with diseased poultry while the other two did not. All cases presented with more than 39.5 ֯ C fever and chills. Additionally, significant increases in C-reactive protein, ferritin, creatine kinase, and lactate dehydrogenase were observed in all cases, while absolute lymphocyte count decreased. Case 2 also had increased calcitonin levels. Acute respiratory failure occurred during the treatment of case 1 and case 2, leading to tracheal intubation and ventilator-assisted ventilation. Unfortunately, case 2 passed away due to sepsis and multiple organ dysfunction, while the other cases had a positive prognosis. Conclusion: mNGS facilitated the early diagnosis of psittacosis pneumonia. It is important to note that there is still a substantial risk of human-to-human transmission in psittacosis pneumonia. Absolute lymphocyte count and calcitonin levels can predict the severity and prognosis of the disease.